Social interactions between Lactobacillus iners and Gardnerella vaginalis biofilms: an unexpected friendship in the bacterial vaginosis ecosystem - Castro, Joana Isabel Reis (2017)
Microbiotec'17 - Congress of Microbiology and Biotechnology 2017